The Role of Digital Twins in the Fulfilment Logistics Chain. Issue 2 (2020) - Piancastelli, Cosimo; Tucci, Mario
Abstract: Although Digital Twins has gained great momentum in the last few years, even being developed in the scenario of manufacturing systems, scarce attention has been devoted till now to the Logistics Digital Twin (LDT). In this paper we describe the first efforts to define the requirements and derive from them the architecture and framework for LDT for fulfilment centres. The analysis stems from actual logistics platforms, for internet orders fulfilment and will use them as verification, validation and accreditation (VV&A) testbed.